KUALITAS PELAYANAN PUBLIK PEMBUATAN IZIN GANGGUAN DI KANTOR BADAN PELAYANAN PERIZINAN KOTA PONTIANAK - Peanta E42009079, Sella Ursulla Nadia (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
This essay making for see how far the service quality in BP2T Pontianak City. The title of the essaybased on the phenomenon that often happen in process making of Hinder Ordonantie. The real problemabout the making of Hinder Ordonantie need more time than written in the SOP. Beside that, PontianakCity was a service and trade city and BP2T was the only one agency that making all of the licensing inPontianak City, so we hoping BP2T can gave the best service to making of the license and HinderOrdonatie is one of the licenses. Based on the phenomenon, this research using qualitative research withdescriptive method. The subject are employers in BP2T Pontianak City and peoples who making thisHinder Ordonantie. In this research, using three technics of collecting data, they are interview technic,observation technic and documentation technic. The result of this research that the service quality fromBP2T is not really optimal and need improvement from the security side, accurate side, responsible side,infrastructure side and hospitality and polite. If one of the side hampered will cause the long timemaking of Hinder Ordonantie.Â Keyword : Service, People and Hinder Ordonantie.